Challenges in Diagnosis of Primary Classical Hodgkin Lymphoma of Parotid Gland by Fine Needle Aspiration: A Rare Case Report and Review of the Literature - Yang, MD, Zhongbo; Esebua, MD, Magda (North American Journal of Medicine and Science, 2016)
Primary Hodgkin lymphoma (HL) arising in the parotid gland is extremely rare and only accounts for 4% of primary lymphomas of the salivary glands. The nodular lymphocyte predominance HL (NLPHL) is the most common subtype. Fine needle aspiration (FNA) has a great potential in diagnosis of non-Hodgking lymphomas (NHL), especially in combination with flow cytometry. However, it is challenging to diagnose HL by FNA due to obscuring reactive inflammatory cells and scant cellularity associated with fibrosis. Primary HL of the parotid has a good prognosis following treatment with chemotherapy and radiation. Here we report a rare case of primary classical HL (CHL), nodular sclerosis type, arising in the parotid of a 73-year old male who presented with a painless parotid mass and no lymphadenopathy at other sites. In this case, the diagnosis was made on the surgical specimen following parotidectomy. The FNA of the parotid mass prior to the surgery was misinterpreted as carcinoma mainly due to the scant cellularity, Reed-Sternberg (R-S) cells mimicking poorly differentiated carcinoma cells, and the extremely low occurrence of HL in the parotid. The patient underwent chemotherapy and radiation after parotidectomy and has been doing well. In conclusion, primary HL of the parotid is extremely rare, and it is very challenging to make a definitive diagnose of HL by FNA. Despite the difficulties in diagnosis, primary parotid HL has a good prognosis compared to other parotid malignancy. It is important for pathologists and surgeons to be aware of this extremely rare entity. [N A J Med Sci. 2016;9(2):83-87. DOI: 10.7156/najms.2016.0902083]